NAVIGATING HALAL CERTIFICATION: KEY FACTORS INFLUENCING LOMBOK SMES’ COMMITMENT TO COMPLIANCE - Ferdaus, Nadia Nuril; Amrullah (Elastisitas : Jurnal Ekonomi Pembangunan, 2024)
This study aims to analyze the influence of Halal Knowledge, Halal Certification Understanding, and the Attitude of MSME (Micro, Small, and Medium Enterprises) Actors towards Halal Certification on the Interest in Halal Certification among MSMEs in Lombok. A quantitative approach with survey methods was used to collect data from 111 MSME respondents in the food and beverage sector. Multiple linear regression analysis showed that, simultaneously, the three independent variables significantly influenced the interest in halal certification. However, partially, only the Attitude of MSME Actors had a significant influence, while Halal Knowledge and Halal Certification Understanding did not have a significant effect. These findings suggest that although MSMEs have good knowledge and understanding of the halal concept and certification, their attitude toward halal certification is the most decisive factor in influencing their interest in applying for certification. Therefore, further efforts are needed to improve the positive attitude of MSME actors toward halal certification to strengthen the halal industry in Lombok.